Managing behaviour in the lifelong learning sector - Wallace, Susan; Wallace, Susan; Sage eBooks (Exeter : Learning Matters, 2007)
This edition provides clear advice and practical ideas on how to manage and motivate students, a key part of achieving QTLS. Fully updated to include the new standards from LLUK, it takes account of the variety of contexts within the lifelong learning sector and links to recent and current learning theory.
Previous ed. published as: Managing behaviour and motivating students in further education. 2002.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Motivation in education; Achievement motivation in youth; College students -- Psychology; College teaching; Effective teaching; Classroom management; Electronic books